Identifying noise sources governing cell-to-cell variability. Issue 8 (April 2018) - Mitchell, Simon; Hoffmann, Alexander
Abstract: Phenotypic differences often occur even in clonal cell populations. Many potential sources of such variation have been identified, from biophysical rate variance intrinsic to all chemical processes to asymmetric division of molecular components extrinsic to any particular signaling pathway. Identifying the sources of phenotypic variation and quantifying their contributions to cell fate variation is not possible without accurate single cell data. By combining such data with mathematical models of potential noise sources it is possible to characterize the impact of varying levels of each noise source and identify which sources of variation best explain the experimental observations. The mathematical framework of information theory provides metrics of the impact of noise on the reliability of a cell to sense its environment. While the presence of noise in a single cellular system reduces the reliability of signal transduction its impact on a population of varied single cells remains unclear. Highlights: The sources of non-genetic variability can be identified and quantified. Modeling enables study of how molecular noise impacts biological function. Intrinsic noise limits channel capacity of signal transduction in single-cells. The impact of single-cell noise on the population deserves further study.